Assessing the Feasibility of Smartphone Apps for HIV-Care Research with MSM and Transgender Individuals in Mpumalanga, South Africa. (September 2017) - Daniels, Joseph; Lane, Tim; Struthers, Helen; Maleke, Kabelo; Moges, Winta; McIntyre, James; Coates, Thomas
There is an urgent need to develop the HIV treatment cascade for men who have sex with men (MSM) and transgender individuals in rural Mpumalanga, South Africa. Mhealth tools such as smartphone applications have the potential to support HIV self-care behaviors. We conducted an exploratory study with HIV-positive community leaders to understand their current uses of cell phones and smartphones and to assess their interest in an HIV research study that utilized a smartphone application for HIV care support. A total of 18 community leaders were recruited to complete a questionnaire and focus group. We found that a large proportion of participants had smartphone access and were interested in a research study that utilized a smartphone application with secure access measures. We conclude that smartphone applications for HIV care research are feasible based on access and interest by MSM and transgender individuals in this rural setting.